2018
DOI: 10.1002/jcb.27459
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐490‐5p inhibits the stemness of hepatocellular carcinoma cells by targeting ECT2

Abstract: To explore the targeting relationship between miR-490-5p and ECT2 in hepatocellular carcinoma (HCC) and the influences of miR-490-5p and ECT2 on the stemness of HCC cells. The expressions of miR-490-5p and ECT2 in HCC tissues and adjacent tissues were identified by quantitative real-time polymerase chain reaction (qRT-PCR). The relationships between the expression levels of miR-490-5p/ ECT2 and the overall/disease-free survival (OS/DFS) of patients with HCC were evaluated using correlative curves. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The activation of the ECT2/Rho pathway may promote the progression of several tumors 7 . ECT2 may promote the progression of human HCC by regulating the Rho/ ERK signaling axis [8][9][10] . ECT2 also plays a tumorpromoting role in a number of other cancers, such as non-small cell lung cancer and breast cancer [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the ECT2/Rho pathway may promote the progression of several tumors 7 . ECT2 may promote the progression of human HCC by regulating the Rho/ ERK signaling axis [8][9][10] . ECT2 also plays a tumorpromoting role in a number of other cancers, such as non-small cell lung cancer and breast cancer [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence favours the notion that miRNAs regulate cancer progression, and several studies have suggested that some miRNAs regulates tumour progression by targeting ECT2. For instance, Yu et al [17] and Fang et al [54] have shown that MiR-490-5p could repress the metastasis and stemness of hepatocellular carcinoma cells by downregulating ECT2 expression. Xu et al [55] have reported that the downregulation of ECT2 by miR-223 induces the expression of p21 and p27, which restrain cell cycle progression and proliferation in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the aberrant overexpression of ECT2 may have protumorigenic effects. Indeed, growing evidence suggests that ECT2 is frequently overexpressed in various cancers and serves as an oncogene [15][16][17][18]. Moreover, numerous clinical studies have shown that high ECT2 expression is associated with adverse clinicopathological characteristics, such as poor tumour differentiation, larger tumour size, positive lymphatic metastasis, and advanced disease stage, and as well as an unfavourable prognosis in multiple type of cancers [11,15,[19][20][21][22][23][24][25], further suggesting that it is a promising prognostic biomarker in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides miR‐490‐3p, low levels of miR‐490‐5p have been associated with a poor outcome in hepatocellular carcinoma (overall survival and disease‐free survival and correlated with lymph node metastasis, primary tumor stage, TNM stage, the recurrence rate at early TNM stage, age, tumor size, alpha‐fetoprotein, hepatitis B antigen, and portal vein thrombosis; Fang et al, 2018; Xu et al, 2017; Yu et al, 2019), neuroblastoma (overall survival and correlation with grade and lymph node metastasis; J. Wang et al, 2020) and pharyngolaryngeal cancer (overall survival; Abdeyrim et al, 2019). Also, miR‐490 downregulation has been correlated with disease progression in hepatocellular carcinoma (Ding et al, 2020; P. Wu et al, 2019) and non‐small cell lung cancer (Dong et al, 2020).…”
Section: Prognostic and Diagnostic Potential Of Mir‐490mentioning
confidence: 99%